2011
DOI: 10.1007/s10103-011-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-level laser therapy in the management of pain, facial swelling, and postoperative trismus after a lower third molar extraction. A preliminary study

Abstract: Pain, swelling, and trismus are the most common complications after surgical removal of impacted lower third molars. The aim of this study was to evaluate the analgesic and anti-inflammatory effects of a low-level laser therapy (Laser Smile™, Biolase®, San Clemente, USA) applied to the wound appeared after the surgical removal of impacted lower third molars. A prospective, randomized, and double-blind study was undertaken in 20 healthy patients with two symmetrically impacted lower third molars. The applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
119
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 38 publications
2
119
2
8
Order By: Relevance
“…14 In a clinical trial, the assessment of analgesia and anti-inflammatory effects of low-level laser has revealed that it has no effect on swelling and pain reduction and improvement of trismus after impacted third molar surgery. 15 In another study, laser therapy could slightly, but not significantly, reduce pain, swelling and trismus. 16 Some studies have shown that LLLT has useful impact on the management of pain and swelling.…”
Section: Discussionmentioning
confidence: 95%
“…14 In a clinical trial, the assessment of analgesia and anti-inflammatory effects of low-level laser has revealed that it has no effect on swelling and pain reduction and improvement of trismus after impacted third molar surgery. 15 In another study, laser therapy could slightly, but not significantly, reduce pain, swelling and trismus. 16 Some studies have shown that LLLT has useful impact on the management of pain and swelling.…”
Section: Discussionmentioning
confidence: 95%
“…However, the number of patients who were evaluated did not represent great expressiveness, in comparison to the number of people who go through this type of procedure every year. From the results, it was suggested that the laser therapy used in these studies was not efficient to reduce the pain state and the swelling, but it was benefic to minimize the trismus 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The study included 10 trials published in the period from 1990 to 2011, with 581 patients evaluated with the goal to answer whether the adjuvant use of laser was efficient or not for such complications 23 . There were no restrictions regarding the patients characteristics, type or administration regime of LLLT and of the measuring methods of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations